Citra Merek Dan Persepsi Kualitas Produk Meningkatkan Keputusan Pembelian Yang Dimediasi Minat Beli (Survei Pada UMKM Kuliner Di Kab. Berau) - Rizki, Muhammad; Zulfikar, Taufik; Djogo, Y Ony; Nurmartiani, Erika; Yuliaty, Farida (Universitas Pahlawan Tuanku Tambusai, 2025)
This research aims to examine the impact of brand image and perceived product quality on purchase decisions, with purchase intention acting as a mediating variable in the context of culinary Micro, Small, and Medium Enterprises (MSMEs). The sampling method employed was probability sampling with a simple random sampling technique, resulting in a total of 400 respondents. Data analysis was conducted using path analysis. The findings reveal a significant simultaneous influence of brand image and perceived product quality on purchase decisions through the mediating role of purchase intention. Additionally, brand image and perceived product quality were found to have a significant partial effect on purchase intention. The study further confirms a positive and significant relationship between purchase intention and purchase decisions.